Житло чи інше володіння особи як об’єкти проведення обшуку в кримінальному провадженні - Левін, В. І.; Levin, V. I. (Вісник Луганського держаного університету внутрішніх справ ім. Е. О. Дідоренка. – 2017. - № 3(79). - С. 248-254, 2017)
У статті здійснено теоретичне та законодавче тлумачення понять житла чи іншого володіння особи як об’єктів проведення обшуку в кримінальному провадженні. Звернено увагу на окремі проблемні питання законодавчого унормування цих дефініцій, що на практиці призводить до труднощів під час проведення обшуку.

The article provides theoretical and legislative interpretation of the concepts of housing or other possession of a person as objects of search in criminal proceedings. A particularly important achievement of the science of the criminal process in the light of the sharp discussions of scholars regarding the definition of the concepts «dwelling» and «other possession of a person» can be considered their legislative consolidation, the definitions of which, basically, are written taking into account the theoretical developments and the practice of the European Court of Human Rights. However, even the legislative consolidation of these terms did not put an end to the discussion on this issue, which necessitates an analysis of these time-base searches. However, in part 2 of Article 234 of Criminal Procedure Code of Ukraine, it is noted that the search is based on decision of the investigating judge. The rules for the search are defined by the provisions of the article 236 of Criminal Procedure Code of Ukraine. Also considering the inspection as an independent investigative action (Article 237 of Criminal Procedure Code of Ukraine), the legislator says only that the inspection of housing or other property is under the rules envisaged for the search of a dwelling or other property. In order to resolve this situation, it would be advisable to fix legally the possibility of inspection of scene in a dwelling or other property without the approval of investigating judge and also make changes to the Criminal Procedure Code, clearly anticipating with the consent of the owner of an overview of housing or other property may be carried out without appealing to the court. Equally important is the proper settlement of the issues related to the proceedings, including enforcement actions in the home or other person’s property. Such investigative (detective) effect is a search that has similarities with investigative review.

В статье осуществлено теоретическое и законодательное толкование понятий жилья или иного владения лица как объектов проведения обыска в уголовном производстве. Обращено внимание на отдельные проблемные вопросы законодательного нормирования этих дефиниций, что на практике приводит к трудностям при проведении обыска.
Housing or Other Person’s Possessions as the Objects of the Search in Criminal Lawsuit
Жилье или другое владение лица как объекты проведения обыска в уголовном производстве
Keywords: кримінальне провадження; обшук; житло; інше володіння особи; практика Європейського суду з прав людини; тимчасове обмеження конституційних прав і свобод людини; criminal proceedings; search; dwelling or other private property of a person; practice of the European Court of Human Rights; temporary restriction of constitutional human rights and freedoms; уголовное производство; обыск; жилье; другое владение лица; практика Европейского суда по правам человека; временное ограничение конституционных прав и свобод человека